New South Wales Family Endowment Act, 1927 - Brown, Douglas V. (Quarterly Journal of Economics, 1928)
Journal Article New South Wales Family Endowment Act, 1927 Get access Douglass V. Brown Douglass V. Brown Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 42, Issue 3, May 1928, Pages 500–507, https://doi.org/10.2307/1884790 Published: 01 May 1928